The Effect of Strategic Leadership On Sustainable Competitive Advantage - Kartika, Levina (International Research Journal of Business Studies, 2023)
This research aims to analyze and identify the effect of strategic leadership on sustainable competitive advantage. This study uses quantitative method with descriptive and associative research. The population includes employees of PT X (heavy equipment trading company), with a sample of 30-500 respondents. The results show that strategic leadership has a positive effect on sustainable competitive advantage applied by respondent. Testing the strategic leadership effect on sustainable competitive advantage produced a significance value of 0.000 < 0.05, with a correlation coefficient value of 0.927. It can be concluded that strategic leadership has a strong influence on sustainable competitive advantage, with a correlation coefficient value of 0.927. Within this study, the majority of respondents expressed agreement with the questionnaire statement in this research regarding the strategic leadership variable, with 16 statement indicators submitted by the researcher and the sustainable competitive advantage (Y) variables, with 14 statement indicators submitted by the researcher.